Model Edukasi Bagi Ibu Rumah Tangga Dalam Mengelola Sampah Di Kecamatan Koto Tangah - Anggun Dwi Utami; Muhammad Alfi (Universitas Prof. Dr. Hazairin, S.H, 2021)
The purpose of this study is to describe trash management in housewives, identify obstacles of managing trash and formulate an educational model in managing trash for housewives at the Koto Tangah District. The type of research used is research and development with a qualitative approach and supported by using ISM (Interpretative Structural Modeling) analysis techniques. The results showed that (1) trash management at the Koto Tangah District was still low. In general, housewives in Koto Tangah sub-district have less knowledge in terms of trash management (2) The obstacles faced by housewives at the Koto Tangah District include the development of technology that is still low lack of trash management to improve people's lives, lack of supervision and implementation of regulations related to trash management, lack of community participation in trash management. (3) The design of the educational model in trash management is formulated with ISM analysis. The results of the analysis of the data obtained, there are elements that have greater thrust in the design of the trash management educational model, namely: Independent trash management system, using the principle of 5R + 1FS and product results from the educational model in trash management is a brochure.